Mantenimiento preventivo, predictivo y correctivo a través de la comparativa de las maquinarias en obras de vialidad - Varela Rivera, Anthony Xavier (2024)
The present research work responded to the following general problem: How will preventive, predictive and corrective maintenance influence the behavior of heavy machinery? The general objective was formulated: "Compare the performance of heavy machinery through preventive, predictive maintenance and corrective for road works” and the Idea to be defended is: The comparison of the different types of maintenance that will allow obtaining the performance of heavy machinery in more efficient road works. The general research method is descriptive due to the behavioral orientation of preventive, predictive and corrective maintenance that would balance the efficient and excellent search when carrying out work on the roads. The population is defined by the payroll of the Project that was found as an example of a numerical project where the value of 92 collaborators of the construction company is taken. The interview technique was applied to the work personnel whose results identified the need to carry out a comparative analysis of the maintenance to be applied to the machinery that is taken as examples to identify its performance and cycle time that needs change, cleaning or repair. In conclusion, in the investigation it was detected that when equipment is used for construction it changes significantly, particularly when it serves to reduce the optimal state that they present in their time, day and work month that form an adequate work schedule in the civil project.